Strategi Meningkatkan Kepercayaan Publik (Studi Kasus: Bea Cukai Tanjung Perak) - Wulansari, Reza Fiolentina Zafira; Claretta, Dyva (Universitas Batanghari Jambi, 2024)
Public relations is an important part of any organization or agency. This is because the activities carried out by public relations professionals aim and focus on building and maintaining a company's brand image and maintaining the reputation of the agency or organization in the eyes of the public. Providing understanding to the public requires parties responsible for providing information that connects organizations or agencies with the public. This party is none other than a PR or public relations practitioner. Apart from realizing that public relations plays an important role in building the image of an organization, the presence of public relations in the field of customs and excise is also recognized as a priority need. Customs and Excise Socialization functions to further strengthen community relations through the implementation of policy outreach regarding customs and excise. Customs and Excise Public Relations also relies on media to communicate with the public, including advertising, social media, and providing information on the latest developments in the customs sector. Public relations theory, public relations strategy, and social media are the theories examined in this research. This research uses descriptive qualitative research methods to collect data in the form of interviews and observations.